A Study on Effects of Multimodal Science Text Design on Meaning-Making of Science Content: Science Teachers’ Perspectives - Ayık, Zekai; Coştu, Bayram (Universitas Pendidikan Indonesia, 2021)
Numerous studies demonstrated that the meaning-making of scientific knowledge is affected by the design of multimodal science texts. Various modes are co-operated together in certain inter-semiotic mechanisms to produce meaning in multimodal texts. Based on this perspective, this research seeks to investigate the effect of mode level in science texts and compositional arrangement on the meaning-making of science concepts and processes. In this context, four science texts with the same content (transformation of energy) at different mode densities and two science texts with the same content (covalent bonding) one of which is arranged in accordance with variation theory of learning are designed. By using the case study method, this research explored six experienced science teachers’ views about the effects of mode level and multimodal text composition on meaning-making. The data were collected with semi-structured interviews. The thematic analysis was employed for data analysis. The findings demonstrated that mode density may affect meaning-making and so learning since different modes have affordance to represent different meaning and meaning relationship types. Besides, multimodal text composition may foreground the critical aspects of content, and help to design a coherent multimodal science text.